2018
DOI: 10.7150/jca.23151
|View full text |Cite
|
Sign up to set email alerts
|

The Unknown microRNA Expression of Male Breast Cancer. Similarities and Differences with Female Ductal Carcinoma. Their Role as Tumor Biomarker

Abstract: Mature microRNAs (miRNAs) are small non-protein coding RNAs that modulate gene expression after transcription. Few studies have shown that male breast cancer (MBC) shows distinctive miRNAs pattern, suggesting its relevance in this pathology. To study this, we performed a profile of 800 miRNAs in 9 MBC samples and in normal epithelial cells of 3 MBC cases.Experimental Design: Of FFPE tissues, miRNA was extracted for profiles using the NanoString method. miRNAs were obtained by comparing tumor samples versus nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…microRNA (miRNA) is an endogenous non-protein-encoded small RNA, located in eukaryotic cells and approximately 22 nt in length. Studies have shown that its expression has a certain impact on the occurrence, development, invasion, metastasis and prognosis of many malignant tumors, which has an important effect in inhibiting tumors or promoting tumor development (8). miRNA has a great significance in the diagnosis and treatment evaluation of NSCLC and can be used as a non-invasive biomarker for prognosis (9).…”
Section: Introductionmentioning
confidence: 99%
“…microRNA (miRNA) is an endogenous non-protein-encoded small RNA, located in eukaryotic cells and approximately 22 nt in length. Studies have shown that its expression has a certain impact on the occurrence, development, invasion, metastasis and prognosis of many malignant tumors, which has an important effect in inhibiting tumors or promoting tumor development (8). miRNA has a great significance in the diagnosis and treatment evaluation of NSCLC and can be used as a non-invasive biomarker for prognosis (9).…”
Section: Introductionmentioning
confidence: 99%
“…The mature miRNAs were detected and quantified by quantitative reverse‐transcription polymerase chain reaction (PCR) in conjunction with TaqMan miRNA assays (Applied Biosystems, Foster City, CA, USA) as described previously . Triplicate RNA samples were used.…”
Section: Methodsmentioning
confidence: 99%
“…Only miRNAs with non-negative counts across all samples were retained for downstream analysis. The relative miRNA levels were indicated as median fold changes and a cutoff of two fold-change (up or down) was used 24 . A Venn diagram was prepared using FunRich 3.1.3 open source software 25 , 26 .…”
Section: Methodsmentioning
confidence: 99%